2022
DOI: 10.1177/14686783221090377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano bentonite on direct yellow 50 dye removal; Adsorption isotherm, kinetic analysis, and thermodynamic behavior

Abstract: Developing countries suffering from the toxicity of different industrial effluents especially dyes. This study successfully prepared and characterized nano-bentonite for anionic dye removal (DY 50). The prepared nanoparticles were characterized by X-Ray Diffraction (XRD), X-ray Fluorescence (XRF), Scanning Electron Microscope (SEM), EDAX analysis, FT-IR, and TGA and the obtained results indicated the formation of nanoparticles with an average size of 15 nm. The effect of different operating conditions was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Kinetic studies for the adsorption of bimetallic Fe/Cu nanoparticles are shown in Tables 2 and Fig. 8 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic studies for the adsorption of bimetallic Fe/Cu nanoparticles are shown in Tables 2 and Fig. 8 45 .…”
Section: Resultsmentioning
confidence: 99%
“…The entropy value (ΔS) is also said to be the degree of disorder explaining the degree of disorder increases with increasing entropy value. entropy has a value of zero so that the reaction runs regularly which is concluded without any significant disturbance (Mahmoud, 2022). Gibbs free energy (ΔG) describes the spontaneity with which the reaction proceeds.…”
Section: Figure 5 Pfo and Pso Kinetic Model Of Cellulosementioning
confidence: 99%
“…The diffraction angle (2) was measured in steps of 0.0167° and varied from 5° to 70°. The produced nanoparticles' crystallite size was determined using the Scherrer equation (Equation 3) [30,38,39].…”
Section: 4nzvi Characterizationmentioning
confidence: 99%